COMPATIBILITY OF BEAUVERIA BASSIANA (BALS.) VUILL ISOLATES WITH SELECTED INSECTICIDES AND FUNGICIDES AT AGRICULTURE SPRAY TANK DOSE - Challa, Murali Mohan; SANIVADA, SANTOSH KUMAR (Innovare Journal of Agricultural Sciences, 2014)
The effects of six commonly used chemical pesticides in which three are insecticides namely quinolphos, monocrotophos, cypermethrin and three fungicides carbendazim, cooper oxychloride and mancozeb on germination, mycelial growth of thirty isolates of Beauveria bassiana was studied. Except mancozeb all the insecticides and fungicides doesn't show a significant inhibition effect on the germination of conidia. There was significant inhibition of mycelia growth in few isolates with insecticides as well as fungicides except copper oxychloride. Copper oxychloride promoted the mycelia growth in many isolates where as mancozeb inhibited the mycelia growth of all the isolates tested in the present study. This work suggests that the most appropriate insecticide and fungicides for use in Integrated Pest Management Programs in combination with Beauveria bassiana isolates. It is important to test the compatibility of isolates of entomopathogenic fungi with the pesticides commonly used in IPM programmes.Â 